PREVALENCE OF NON-CLASSIC GALACTOSEMIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Helena Vaz Tolloto, Gilce; Saragiotto, Laiz (Health and Society, 2022)
Galactosemia is an inborn error of metabolism, caused by autosomal recessive deficiency in enzymes that convert galactose to glucose. Excess galactose is converted in the liver to galactitol (alcohol of elevated toxicity), responsible for neurologic, hepatic, gastrointestinal manifestations, in varying degrees according to the mutation developed. OBJECTIVE: To observe the prevalence of galactosemia in patients with DM1 and DM2. METHODS: Group 1: patients with DM2, male gender (n=9); female gender (n=11). Group 2: patients with DM1, male gender (n=7); female gender (n=3). Group 3: Non-diabetics (n=30). Clinical follow-up of these patients included laboratory tests and imaging studies. RESULTS: There was a higher prevalence of galactosemia in DM2 patients, in comparison to DM1 patients and non-diabetics (21.66 >3.33 >1.66). The prevalence of galactosemia in DM2 patients was higher than that found in DM1 patients (2166 >3.33). CONCLUSION: Our study found a higher prevalence of galactosemia in DM2 when compared to DM1 and a healthy population.